Long-run effects of super low fertility on housing markets - Lee, Jangyoun; Suh, Hyunduk (Economic modelling, 2025)
The total fertility rate (TFR) in Korea fell to the historically lowest value of 0.72, reaching the state of super low fertility, also similarly observed in other East Asian countries. We quantitatively assess future implications of super low fertility on housing markets using an overlapping generations (OLG) general equilibrium model, which features housing markets and demographic transitions. The results predict that while the current housing boom will continue in the near future, real housing prices will eventually decline after 2035 because of low fertility. Among government policies, increasing the housing supply or the birth rate can mitigate this long-term housing boom-bust cycle and is welfare-improving for currently young generations. Meanwhile, stricter caps on the LTV ratio are ineffective in stabilizing the housing cycle and welfare-reducing except for older generations. •East Asian countries are entering a stage of super low fertility.•We analyze the the effects of super low fertility on Korean housing markets.•We employ an OLG model with housing markets and demographic transitions.•The results predict that the housing price will decline after 2035.•We also analyze the effect of government policies on housing markets.